**Answer:**

y = -4(x²+ 1)

**Step-by-step explanation:**

We can factor out -4

y = -4x²-4

y = -4(x²+ 1)

This cannot be factored further, because x²+ 1 cannot be factored

**Answer:**

7

**Step-by-step explanation:**

x2 + 5x - 7

sub x = 2 in

(2 X 2) + (5 X 2) - 7

4 + 10 - 7

= 7

the multiplication is factor and the division quotient

**Answer:**

**Step-by-step explanation:**

There's a calculated explanation below. I hope this helps!

C is the correct answer i had this question and got it right